British and Western literature : a thematic approach - Carlsen, G. Robert, 1917-; Gilbert, Miriam (New York : Webster Division, McGraw-Hill, 1985)
A thematically arranged anthology of poems, short stories, plays, and novellas from western literature for the twelfth-grade reader.
Includes indexes.
Keywords: Literature -- Collections; English literature; Literature -- Collections